(untitled) (Bangladesh Journal of Medical Education, 2018)
This was a descriptive cross-sectional study conducted in 2015, objective was to find out the views of the students of 3rd phase of non-government medical colleges regarding the community based medical education practice in their colleges. Data was collected from 507 students of 12 medical colleges by using self-administered structured questionnaires. Among the students 223 were from the Dhaka city and 284 from outside the Dhaka city. Almost 90 percent of the students mentioned that their institutes conducted RFST and Day Visit programe, and duration of Residential Field Site Training (RFST) programe ranges from 1-30 days with mean 9.45 and SD ± 6.34. Most of the students mentioned that they did not stay night in the community. About sixty percent of the students were satisfied with the RFST programe . During RFST programme most of the students 387 (77.7) visited upazila health complex, and 296 (59.4) participated in the conduction of survey. Most of the students visited institute of public health, EPI head quarter and MCH centre or clinic during Day visit programme. Most of them mentioned problems faced in RFST programme as: lack of transport support; lack own accommodation facilities; lack of security; and lack of cooperation from the authority of the different organizations. Suggestions given by the students for the further improvement of the practice of CBME programme in their institutes were mainly : realization of importance of CBME by college authority , teachers and students; College authority should be well motivated for conducting the CBME programme activities in their institute; College authority should build dormitories for the permanent solution of the residential problems and College authority should have the required amount of transport for this activities. Bangladesh Journal of Medical Education Vol.9(1) 2018: 21-25